PRAKTIK AKUNTANSI PADA BISNIS RETAIL: SEBUAH STUDI FENOMENOLOGI - Laily, Nujmatul (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2013)
The purpose of this research is to understand the implementations of Accounting in Small and Medium Enterprise (SMEs). Therefore, this research is developed based on interpretive paradigm. Phenomenology is used to explore comprehensive meaning of accounting practice in Small and Medium Enterprise (SMEs). The result shows that Small and Medium Enterprise (SMEs) doesn’t have a formal bookkeeping (accounting) to operate their business. It is caused by their assumption that having bookkeeping (accounting) is not efficient and make dificulities for them. Beside that, they don’t have knowledge and skill to do that activity (bookkeeping/accounting).